The Role of Knowledge as a Mediating Variable in the Effect of Promotion on Customers’ Purchase Decisions and its Review from the Islamic Economics Perspective (Evidence from the Customers of Surya Akbar Housing,Tanjung Barangan,Palembang,South Sumatra) - Malikal Mulki Octadyla (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to analyze the effect of promotion on customers’ purchasing decisions through knowledge as the mediating variable and then deliver a review from the Islamic economics perspective. We used quantitative approach and afterwards conducted a discussion to review the results from the perspective of Islamic economics using a qualitative approach. The data collection technique utilized primary data by handed out questionnaires and interviewed customers of a housing project in Palembang city, South Sumatra, Indonesia. From the total population of 270 customers, we selected 115 respondents by using saturated sampling technique. The data analysis technique used classic assumption test, path analysis, and causal step to test the effect of mediating variable in the model. Data were being processed using SPSS version 2.1. The results of this study indicated that promotion has a positive and significant direct effect on purchasing decisions. Promotion also has a positive and significant effect on knowledge, whilst knowledge has a positive and significant effect on purchasing decisions, and was able to mediate the effect of Promotions on the Customers’ Purchase Decisions. In the final stage of the study, we conducted an interview to the developer company as well as the customers, in order to discuss the results of this study from the Islamic Economics Perspective. We discovered that the housing developer company has been running their business in accordance with the Islamic law, as for their customers, we found that they were already have sufficent knowledge regarding the products of the developer company.